Perancangan Enterprise Architecture HMI Sampit Menggunakan TOGAF - Amelia Wulan Sari Sapitri (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
The Islamic Student Association (HMI) is an umbrella organization with a clear model of being Indonesian and Islamic, providing a platform to train and develop leaders with honesty and quality determination, faith and responsibility. The factors that provide direction within the organization to adopt an Enterprise Architecture (EA) system are aimed at enhancing what the organization needs. Enterprise architecture or what can be called Enterprise Architecture (EA) is a description of the task in question consisting of knowledge, actions, direction from the organization and architectural performance parameters in the description of the design or plan and development of an integrated system. TOGAF (The Open Group Architecture Framework) is a framework that is widely used in creating enterprise or organizational architectures. TOGAF offers methods and tools for creating, running, implementing, and maintaining enterprise architectures in existing systems. The results of this study are in the form of a blueprint that is expected to be useful for organizations as material to assist IT development in HMI.